The Effect of Integrated Marketing Communication on the Buying Decision of Halal Products View of Different Generation Customers in Bangkok - Witoowinit , Woraya; Intuluck, Watit (Dusit Thani College Journal, 2020)
This research aims to study 1) demographic factors that affect the buying decision of Halal products 2) the integrated marketing communication factors that affect the buying decision of Halal products 3) the role of the generation (X, Y, Z) as a controlling variable between integrated marketing communication factors and purchasing intentions of Halal products. The total sample size of 388 people was drawn from people who were born in the year of 2508 B.E. onwards and live in Bangkok. This research is quantitative research. Data were collected via the developed questionnaire. The research found that the analysis of odds ratio in which integrated marketing communication and generation variables influence the buying decision of Halal products. This can be classified by various types of integrated marketing communication tools including advertising, sales promotion, personal selling, direct marketing, sponsorships and event marketing or special events by using the generation of X, Y and Z as a control variable. In testing of the influence on the decision to buy Halal products, it was found that personal selling and Generation Z influenced the purchasing intentions of Halal products and personal selling and Generation Z had the higher odds ratio to make a decision to buy Halal products than Generation X and Generation Y at 0.406 times (odds ratio = 0.406) with statistical significance level of 0.05. it also found that direct marketing and Generation Z influenced the decision to buy Halal products, that is, the population of Generation Z who received marketing communication through direct marketing have a chance to make a decision to buy Halal products at 0.536 times (odds ratio = 0.536) of Generation X and Generation Y with statistical significance of 0.05